IMPLEMENTATION OF THE POLICY PROGRAM BINA LINGKUNGAN THE GOVERNMENT OF BANDAR LAMPUNG CITY (A Studies on Vocational High School 2 Bandar Lampung) - . Asrudi; M. Ferdiansyah; Sundari Saputri (UBL, 2016)
The problem in this research is, how the implementation of the policy Program Bina Lingkungan of the Government of Bandar Lampung City especially on Vocational High School 2 Bandar Lampung (2) anything that supports and hinders the implementation of the policy Program Bina Lingkungan (3) how the impact The program of students quality, the quality of the school and Teachers. research methods which, according to researchers in accordance with the method of this research is to use the type of qualitative research with descriptive analysis methods, the use of these methods is to describe and assess qualitative, How opinion of executing program ( Teachers and Educational staff ) about the implementation of the policy Program Bina Lingkungan of the Government of Bandar Lampung City especially on Vocational High School 2 Bandar Lampung All data retrieved directly from informants in field by using interviews and Observation . The results showed that the policy of Program Bina Lingkungan of the Government of Bandar Lampung have been implemented, but not optimal yet cause there are problem among them : Data manipulation of the new student Candidate, Decereasing interested of community to school in private school and others.